2016
DOI: 10.17221/254/2015-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between somatic cell count and milk casein level obtained by two different methods

Abstract: Musayeva K., Sederevičius A., Želvytė R., Monkevičienė I., Beliavska-Aleksiejūnė D., Stankevičius R. (2016): Relationship between somatic cell count and milk casein level obtained by two different methods. Czech J. Food Sci., 34: 47-51.The purpose of the present work was to investigate the impact of somatic cell count (SCC) on the content of milk casein and to compare the sensitivity of different methods for the determination of the casein level in milk. Two different methods were employed in order to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…Here, SCC correlated negatively with β-casein (r = −0.325, P < 0.01) and the percentage of caseins in total proteins (r = −0.39, P < 0.01), but it had a highly positive correlation with κ-casein (r = 0.76, P < 0.01). This agrees with Musayeva et al (2016), who found that the percentage of caseins in total proteins decreased when the SCC increased in BM. Subclinical and clinical mastitis are known to be associated with increased activity of plasmin, the major milk proteolytic enzyme (Le Roux et al, 1995;Stelwagen, 2011).…”
Section: Short Communication: Caseins and α-Lactalbumin Content Of Camel Milk (Camelus Dromedarius) Determined By Capillary Electrophoressupporting
confidence: 92%
See 1 more Smart Citation
“…Here, SCC correlated negatively with β-casein (r = −0.325, P < 0.01) and the percentage of caseins in total proteins (r = −0.39, P < 0.01), but it had a highly positive correlation with κ-casein (r = 0.76, P < 0.01). This agrees with Musayeva et al (2016), who found that the percentage of caseins in total proteins decreased when the SCC increased in BM. Subclinical and clinical mastitis are known to be associated with increased activity of plasmin, the major milk proteolytic enzyme (Le Roux et al, 1995;Stelwagen, 2011).…”
Section: Short Communication: Caseins and α-Lactalbumin Content Of Camel Milk (Camelus Dromedarius) Determined By Capillary Electrophoressupporting
confidence: 92%
“…The results showed a weak positive correlation (r = 0.266, P < 0.01) between SCC and total protein, in agreement with previous results (Hamed et al, 2012). Somatic cell count, a quantitative index of mastitis condition of ruminants, has been linked with a decrease in casein content, proteolysis, and changes in the protein fraction distribution in BM (Le Roux et al, 1995;Musayeva et al, 2016;Johansson et al, 2017). Here, SCC correlated negatively with β-casein (r = −0.325, P < 0.01) and the percentage of caseins in total proteins (r = −0.39, P < 0.01), but it had a highly positive correlation with κ-casein (r = 0.76, P < 0.01).…”
Section: Short Communication: Caseins and α-Lactalbumin Content Of Camel Milk (Camelus Dromedarius) Determined By Capillary Electrophoressupporting
confidence: 90%
“…Milk contains a large number of native enzymes with differing specificity, stability and impact on product quality (Kelly & Fox, 2006). Plasmin (EC 3.4.21.7), with its zymogen plasminogen and other parts of the complex enzyme system, constitute the major native protease system in milk, and has been reported to be correlated with udder health, as indicated by the somatic cell count (SCC) (Ramos, Costa, Pinto, Pinto & Abreu, 2015;Musayeva, Sederevičius, Želvytė, Monkevičienė, Beliavska-aleksiejūnė & Stankevičius, 2016). This protease system exhibits a high thermal stability and can remain partially active after the UHT treatment; therefore, the plasmin system has been closely linked to physicochemical deterioration of UHT milk (Kohlmann, Nielsen & Ladisch, 1991;Kelly & Foley, 1997;Rauh et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…It is the richest and appreciable source of energy for infant mammals including human beings [5]. Milk is an excellent source of proteins, fats, vitamins, minerals and antioxidants [6]. It is a versatile ingredient used for the production of many dairy products i.e.…”
Section: Introductionmentioning
confidence: 99%